Potential Impact of Seat Tray Table’s Height Adjustment on Aircraft Passengers’ Comfort During In-Flight Activities - Salim, Salim Mkubwa; Romli, Fairuz Izzuddin; Ozve Aminian, Negin (Journal of Advanced Research Design, 2025)
Most aircraft passengers consider flight comfort as one of their primary selection criteria when choosing their travel option. When aircraft passengers can easily and comfortably perform their in-flight activities, their overall comfort level is also enhanced. In this case, since the seat tray table has been used to support many in-flight activities, the adequacy of its height is important. Furthermore, available legroom at the seat will also affect the required seat tray table height for aircraft passengers to comfortably perform their in-flight activities. Based on this notion, this study intends to establish the influence of seat pitch, seat tray table height and the passengers’ anthropometry parameters on their in-flight comfort level by conducting an activity-based sitting comfort experiment. In this experiment, comfortable seat tray table height is recorded for three common in-flight activities at different seat pitch settings: eating, writing and using laptop. Based on the experimental results, the settings of seat tray table height and seat pitch are shown to notably affect the passengers’ comfort during in-flight activities. Moreover, comfortable seat tray table height is also correlated with passengers’ anthropometry. In comparison to typical height of seat tray table that is currently used in the aircraft cabin, which is 68 cm, the average resultant comfortable height is found to be higher. This indicates a clear mismatch of the seat tray table height and highlights the need for proper adjustment of the seat tray table height to improve passengers’ flight comfort.